2018
DOI: 10.1186/s12887-018-1334-1
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of neonatal case management and outcomes in rural Rwanda post implementation of a national neonatal care package for sick and small infants

Abstract: BackgroundDespite worldwide efforts to reduce neonatal mortality, 44% of under-five deaths occur in the first 28 days of life. The primary causes of neonatal death are preventable or treatable. This study describes the presentation, management and outcomes of hospitalized newborns admitted to the neonatal units of two rural district hospitals in Rwanda after the 2012 launch of a national neonatal protocol and standards.MethodsWe retrospectively reviewed routinely collected data for all neonates (0 to 28 days) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 28 publications
2
14
2
Order By: Relevance
“…From the rest 94 articles, 48 were excluded as a result of not fulfilling our inclusion criteria by reviewing their titles and abstracts. Therefore, 46 full-text articles were accessed and assessed for eligibility based on the inclusion criteria [3,15,17,20,21,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71]. Finally, 13 studies that fulfilled the eligibility criteria were included in the meta-analysis (Figure 1).…”
Section: Characteristics Of Reviewed Studiesmentioning
confidence: 99%
“…From the rest 94 articles, 48 were excluded as a result of not fulfilling our inclusion criteria by reviewing their titles and abstracts. Therefore, 46 full-text articles were accessed and assessed for eligibility based on the inclusion criteria [3,15,17,20,21,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71]. Finally, 13 studies that fulfilled the eligibility criteria were included in the meta-analysis (Figure 1).…”
Section: Characteristics Of Reviewed Studiesmentioning
confidence: 99%
“…In Rwanda, 10% of newborns are born preterm each year and 7% are born with LBW [ 33 ]. Prematurity/LBW and HIE are two of the three leading causes of admission to hospital neonatal care units in Rwanda [ 34 ]. However, to our knowledge, mental health among mothers of children with these perinatal risk factors has not been studied in Rwanda.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study conducted in Ethiopia found that 60.2% of mothers had poor ENC knowledge. [5] Authors of a study in Bangladesh found that mothers were knowledgeable about breastfeeding and thermoregulation, yet identified a gap in cord care. [6] Countries that have shown reductions in newborn deaths, infections, and intensive care unit admissions using ENC has encouraged others to follow the WHO evidencebased guidelines.…”
mentioning
confidence: 99%